2014
DOI: 10.1007/s00210-014-1063-4
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of histidine and aspartic acid phosphorylation in human prostate cancer cells

Abstract: We have developed a method to identify previously undetected histidine and aspartic acid phosphorylations in a human prostate cancer progression model. A phosphoproteome of our cell line model is presented, with correlation of modified protein expression between the three states of cancer: non-tumorigenic, tumorigenic, and metastatic cells. With the described interaction proteins potentially phosphorylated by NM23-H1, cellular responses to motility and conformational change stimuli would be achievable. We dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…We observed significant enrichment of NME1/2 (55-fold) by the 1-pHis mAb column as well as enrichment of PGAM (4-fold) and other known 3-pHis proteins including; histone H4 (22-fold) and ACLY (11-fold). Proteins corresponding to recently identified pHis phosphopeptides (Lapek et al, 2015) including; TUBB, TCP1/CCT1, YWHAB, LDHA, RPS3A and GAPDH were also enriched from 5 to 11-fold (Tables 1 and S1). In all, 630 proteins (58% of proteins quantified in 1-pHis column elutions E1–E3) and 506 proteins (54% of 3-pHis E1–E3) were enriched by at least 2-fold (Table S1) for a total of 786 different proteins.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…We observed significant enrichment of NME1/2 (55-fold) by the 1-pHis mAb column as well as enrichment of PGAM (4-fold) and other known 3-pHis proteins including; histone H4 (22-fold) and ACLY (11-fold). Proteins corresponding to recently identified pHis phosphopeptides (Lapek et al, 2015) including; TUBB, TCP1/CCT1, YWHAB, LDHA, RPS3A and GAPDH were also enriched from 5 to 11-fold (Tables 1 and S1). In all, 630 proteins (58% of proteins quantified in 1-pHis column elutions E1–E3) and 506 proteins (54% of 3-pHis E1–E3) were enriched by at least 2-fold (Table S1) for a total of 786 different proteins.…”
Section: Resultsmentioning
confidence: 94%
“…SILAC ratio (light/heavy) indicates fold enrichment of proteins by pHis mAb affinity purification. Values from two sequential elution fractions (elution 1 [E1] and elution 2 [E2] are reported as the median value of all quantified peptides that correspond to the listed protein. a not expressed in cell line tested; b related protein family members or isoform(s) were enriched; c sequences from pHis phosphopeptides detected by MS (Lapek et al, 2015); - indicates not detected. See also Table S1 and Figure S6.…”
Section: Figurementioning
confidence: 99%
“…The identities of the pHis proteins we identified suggest that pHis may play a role in mammalian cell signaling [32][33][34] . Indeed, a direct correlation of pHis protein levels with carcinogenesis has recently been reported 30,[35][36][37] . Interestingly, we identified 20 N-phosphate sites on proteins that were reported to be enriched by IAP by Hindupur et al from mTOR-driven hepatocellular carcinoma mouse tumors as potential LHPP substrates, including BCLAF1, which in our studies was found to contain pLys (K391) with a reasonable probability of localization of 79.6%.…”
Section: Discussionmentioning
confidence: 95%
“…An alternative strategy of elevating LC pH to 5 (without enrichment) was employed as a compromise between stabilization of pHis and ionization of peptides. 20 pHis phosphopeptides were identified; however, these have not yet been validated at the protein level [65,66]. Negative electron-transfer dissociation (NETD) developed by the Coon lab, which is run under alkaline conditions, is a promising new technique that has the potential to solve these issues [6769].…”
Section: Introductionmentioning
confidence: 99%